2018
DOI: 10.1093/conphys/cox073
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ovarian cycles, pregnancy and post-partum in captive marsh deer (Blastocerus dichotomus) by measuring fecal steroids

Abstract: Lay summary: This study aimed to characterize some aspects of the reproductive physiology of female marsh deer, such as length and fecal progestins profile of estrous cycle, pregnancy and post parturition periods, information that we consider an important and decisive factor for the elaboration of conservation actions of Neotropical deer species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…As observed in other ungulate species (Asa et al, 1996;Khonmee et al, 2014;Ostrowski et al, 2005;Polegato et al, 2018;Thompson et al, 1998), hormonal profiles of oestrous cycles showed higher fPM concentrations during the luteal phase compared to the follicular phase. However, fEM profiles of the female roan antelope did not show significant increases in the follicular phase when compared to the luteal phase.…”
Section: Discussionsupporting
confidence: 76%
“…As observed in other ungulate species (Asa et al, 1996;Khonmee et al, 2014;Ostrowski et al, 2005;Polegato et al, 2018;Thompson et al, 1998), hormonal profiles of oestrous cycles showed higher fPM concentrations during the luteal phase compared to the follicular phase. However, fEM profiles of the female roan antelope did not show significant increases in the follicular phase when compared to the luteal phase.…”
Section: Discussionsupporting
confidence: 76%
“…The values of progesterone concentration of each female from the day after the last day of estrous behavior were considered basal and from these, the mean and standard deviation (SD) were calculated. Values greater than the criterion value (mean + 2SD) were considered indicative of the luteal phase ( Thompson et al, 1998 ; Pereira et al, 2006 ; Polegato et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The animals showed behavioral estrus on average 58 h after the end of the treatment (ranging from 40 to 64 h). Ovulation and formation of the corpus luteum were verified by monitoring fecal progestins [89]. In M. gouazoubira, cloprostenol has also been tested using two injections ten days apart, resulting in 100% (n = 6) of hinds expressing behavioral estrus after 40 to 69 h of the last application [24].…”
Section: Control Of the Estrous Cycle And Artificial Inseminationmentioning
confidence: 99%
“…Females in estrus manifest an increase in the rate of urination, decreased reactivity to the presence of the handlers, lordosis response to the handlers, which is often accompanied by a rapid wagging of the tail (Figure 3A), vulvar hyperemia, and abundant mucoid translucent discharge. Studies have shown the occurrence of such signs in B. dichotomus [89], M. americana [95], and M. nemorivaga [96].…”
Section: Control Of the Estrous Cycle And Artificial Inseminationmentioning
confidence: 99%